Strategic imperatives of the Public development environmental Police of Ukraine - Malysh , Natalia; Moskalenko , Svitlana (Theory and Practice of Public Administration, 2019)
Improving and developing the system of state regulation in the field of ecology is an actual problem for modern Ukraine. This regulation is aimed at implementing the principles of good environmental governance.The most common model of social development is the sustainable development model. It combines three components: the economic, social and environmental spheres. However, researchers in different countries are looking for new models of development that take into account existing resource constraints, unlimited human needs, the pursuit of equitable distribution and consumption.The article defines the main guidelines for the formation of strategic imperatives for the development of public environmental policy in Ukraine. These imperatives are based on the theory of balanced development and the main provisions of regulatory support of environmental policy in Ukraine. The essence and influence of environmental policy direction on the development of the country are substantiated. The activity of the Cabinet of Ministers of Ukraine in the field of ecology is analyzed. It is noted that ecological education is an important component of the implementation of the state environmental policy. The importance of public involvement in environmental management decisions is emphasized.Following the signing of the Association Agreement with the EU, a gradual approximation of environmental legislation to the relevant EU directives is ensured. The main directions of implementation are to build an effective system of public administration in the field of environmental protection, control over the observance of environmental legislation, systematic monitoring of the effects of economic processes on the environment, the implementation of ideas of balanced (sustainable) development, improving the system of environmental education.The main directions of implementation are defined in the Law of Ukraine "On the Fundamental Principles (Strategy) of the State Environmental Policy of Ukraine for the Period up to 2030".Ukraine is already implementing international environmental management standards, environmental product labeling systems, creating national environmental information and analytical systems, and continues to investigate territories contaminated by the Chornobyl disaster.Currently, the following benchmarks for the formation of these imperatives are expressed:- conservation and restoration of recreational, nature conservation areas, which in the conditions of decentralization becomes of particular importance;- the solution of the problem of hazardous waste management, which must be solved by improving technological processes and introducing innovative processing and recycling technologies;- introduction of e-government system and automated information systems of environmental data, which will significantly increase transparency, efficiency and quality of administrative decision-making, respect for environmental rights of citizens.